The SF‐36v2 and SF‐12v2 health surveys in New Zealand: norms, scoring coefficients and cross‐country comparisons - Margreet A. Frieling; Walter R. Davis; Grace Chiang (Elsevier, 2013)
Abstract Objective : To provide New Zealand population norms for version 2 of the SF‐36 and SF‐12 health surveys and report scoring coefficients that enable the construction of Physical and Mental Component Summary scores from New Zealand SF‐36v2 and SF‐12v2 data. Approach : Norms for the SF‐36v2 and scoring coefficients for the Physical and Mental Component Summary scores are estimated using 2006/07 New Zealand Health Survey data, which included 12,488 adults (aged 15 years and over). Norms for the SF‐12v2 are derived from 2008 New Zealand General Social Survey data, including 8,721 adults. Comparisons are made between New Zealand norms for versions 1 and 2 of the SF‐36 instrument. In addition, New Zealand SF‐36v2 and SF‐12v2 norms and the scoring coefficients are compared with those for the United States and South Australia. Conclusion : Differences between: 1) New Zealand population norms for the SF‐36 versions 1 and 2; and 2) SF‐36v2 and SF‐12v2 population norms for New Zealand and those for the United States and South Australia highlight the importance of using version‐specific and country‐specific population norms. Implications: The analysis reported here allows for the appropriate use of the SF‐36v2 and SF‐12v2 instruments in New Zealand.